Key issues of central and local government finance in the People's Republic of China - Zhang Qichun; Li Shufang (Asian Development Bank Institute (ADBI), 2016)
Fiscal decentralization has been established in the People's Republic of China (PRC), but crises emerge at the local government level due to remaining problems of the fiscal administration system of tax allocation and the impact of replacing the business tax with a value added tax. The PRC taxation system requires readjustment and local governments have begun to focus on innovative financing models. The main path to stable and sustainable government finances is to maintain the general public budget and the government fund budget. The present study shows that use of innovative fundraising and financing channels will lead to the upgrading of local government infrastructure and public service. Suggestions for enhancing local government fiscal stability and sustainability include: reducing the fiscal burden at the local level by standardizing and legalizing outlay responsibilities at all government levels; forming a long-term fiscal growth mechanism by establishing a modern taxation system; establishing a standardized and predictable transfer payment system by introducing block transfer payments and prioritized transfer payments as a basis for a stable growth mechanism for general transfer payments; promoting public-private partnership legislation to encourage participation of social capital and maximize the multiplier effect of public expenditure; and improving the mid-term budget and debt-annexed budget and establishing a government planning mechanism for investment and debt financing of major infrastructure construction projects.
Keywords: E62; 330; Local government; fiscal stability; fiscal sustainability; fiscal administration; China's "new normal"